Regulation of the cellular thymidine kinase gene promoter in simian virus 40-infected cells. - Roehl, H H (1993)
We examined the regulation of the cellular thymidine kinase (TK) gene promoter in simian virus 40 (SV40)-infected simian CV1 cells. Nuclear run-on transcription assays demonstrated a three- to fourfold increase in the rate of transcription of the endogenous gene at 14 to 16 h following viral infection. In addition, hybrid genes containing the human TK promoter linked to the bacterial neomycin resistance gene were induced by SV40 in stably transfected cells, indicating that promoter sequences are sufficient to confer viral regulation. Analysis of human TK promoter deletion mutants indicated that sequences localized between -67 and +30 bp relative to the transcriptional initiation site are sufficient to confer regulation on SV40-infected cells. These sequence elements are distinct from those required for serum induction, which were previously localized to the region between -135 and -67. These results suggest that SV40 activates novel cellular pathways that are not activated by serum stimulation of quiescent cells.